2020
DOI: 10.1016/j.simpat.2020.102108
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Simulation of QoS-Aware Service Selection in Cloud Computing

Abstract: Cloud service selection process is significantly challenging and complicated as there are various QoS factors to consider when selecting cloud services. This paper proposes a new QoS-aware selection model systematically and succinctly representing QoS attributes which cloud consumers can easily use and understand when selecting cloud services. In order to ensure the credibility of the cloud service selection, the proposed model collects QoS data from different sources including cloud providers, users' reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…This value will enable detecting all IT services, the functionality of which can match the sub-set ITacm 1 separated at Step 1. 4, at least by 25 % (similar to [16]).…”
Section: Checking the Possibility To Implement An Assessment Of The Degree Of Match Of The Information Technology Services And The Formulmentioning
confidence: 56%
See 3 more Smart Citations
“…This value will enable detecting all IT services, the functionality of which can match the sub-set ITacm 1 separated at Step 1. 4, at least by 25 % (similar to [16]).…”
Section: Checking the Possibility To Implement An Assessment Of The Degree Of Match Of The Information Technology Services And The Formulmentioning
confidence: 56%
“…As it follows from [16], the value of function (4) will aim to 2 if the description of the functional requirements implemented by the reusable IT service perfectly matches the description of the functional requirements for the process or the problem set by a customer.…”
Section: Results Of the Improvement Of The Model Of Precedent Of Automated Business Processmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] One of the main research trends of autonomic computing application is self-adaptive Cloud systems. [7][8][9][10][11][12][13][14] Indeed, within large datacenters running some large-scale applications, the autonomicity of the underlying systems is a key feature to meet the performance, availability and service level agreements (SLAs) while ensuring a cost effectiveness of offered services. During our study, we identified two topics in the context of self-adaptive Cloud systems that got increasing attention over the last years: (a) self-adaptive resource allocation in an on-demand basis and (b) self-healing feature that provides fault-tolerance capabilities.…”
Section: Introductionmentioning
confidence: 99%